2017
DOI: 10.1039/c7ra00097a
|View full text |Cite
|
Sign up to set email alerts
|

In situ construction of Z-scheme g-C3N4/Mg1.1Al0.3Fe0.2O1.7 nanorod heterostructures with high N2 photofixation ability under visible light

Abstract: By tuning the metal ratio, a Z-scheme g-C 3 N 4 /MgAlFeO nanorod composite was prepared in situ. The nitrogen photofixation performance under visible light was tested to evaluate the performance of the prepared catalysts. Strong electronic coupling, as evidenced by the XPS, PL and EIS results, exists between the two components in the g-C 3 N 4 /Mg 1.1 Al 0.3 Fe 0.2 O 1.7 heterojunction photocatalysts, leading to a more effective separation of photogenerated electron-hole pairs and faster interfacial charge tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 48 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…[340][341][342][343] Recently, the photocatalytic activity of production of NH 3 from N 2 and H 2 O (Equation 42) has been much improved by using g-C 3 N 4 based heterostructured photocatalysts and other semiconductors such as BDD. [344][345][346][347][348] The selective conversion of dinitrogen into ammonia was also made possible through plasmon-induced charge separation by using a strontium titanate (SrTiO 3 ) photoelectrode loaded with gold nanoparticles (Au-NPs) and a zirconium/zirconium oxide (Zr/ZrOx) thin film to produce simultaneous stoichiometric amounts of ammonia and oxygen from nitrogen and water under visible-light irradiation (Equation 42). 349 The NH 3 formation action spectrum approximately agrees with the plasmon resonance spectrum.…”
Section: Photocatalytic Production Of Ammonia By Nitrogen Fixation Anmentioning
confidence: 99%
“…[340][341][342][343] Recently, the photocatalytic activity of production of NH 3 from N 2 and H 2 O (Equation 42) has been much improved by using g-C 3 N 4 based heterostructured photocatalysts and other semiconductors such as BDD. [344][345][346][347][348] The selective conversion of dinitrogen into ammonia was also made possible through plasmon-induced charge separation by using a strontium titanate (SrTiO 3 ) photoelectrode loaded with gold nanoparticles (Au-NPs) and a zirconium/zirconium oxide (Zr/ZrOx) thin film to produce simultaneous stoichiometric amounts of ammonia and oxygen from nitrogen and water under visible-light irradiation (Equation 42). 349 The NH 3 formation action spectrum approximately agrees with the plasmon resonance spectrum.…”
Section: Photocatalytic Production Of Ammonia By Nitrogen Fixation Anmentioning
confidence: 99%
“…As-synthesized bismuth monoxide (BiO) materials were applied in the photocatalytic reduction of N 2 to NH 3 under solar light. Research results [28] showed that the NH 3 synthesis rate is up to 1226 mmol•g −1 •h −1 which is about 1000 times higher than that of the Fe-TiO 2 photocatalyst (Table 2). Obviously, deactivation of this photocatalyst did not occur even after being used more than 120 hours.…”
Section: Other Metal Oxide-based Materialsmentioning
confidence: 95%
“…This work highlights the possibility of designing hybrid systems with organic and inorganic semiconductors for N2 photofixation. As mentioned above, construction heterojunction is the preferable approach to elevate the N2 fixation performance of g-C3N4 [241][242][243][244] .…”
Section: N2 Photofixationmentioning
confidence: 99%